2012
DOI: 10.1159/000331648
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia among Chinese Women with Venous Thromboembolism during Pregnancy

Abstract: Aims: To assess the prevalence of thrombophilia among Chinese women with venous thromboembolism (VTE) developed during pregnancy. Methods: Based on information from a tertiary teaching unit, all recorded cases of deep vein thrombosis (DVT) and pulmonary embolism (PE) during pregnancy diagnosed between 1997 and 2005, were assessed for prevalence of thrombophilia. Fifty-five healthy women, who had at least one normal pregnancy but without any previous history of VTE, were recruited as controls. Results: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Of the 32 potentially eligible articles, 18 articles were excluded (reasons presented in Chart 1) and 14 remained for final analysis. Two had overlapping data, leaving a total of 12 eligible studies [4,[11][12][13][14][15][16][17][18][19][20][21]. No studies were added from manual search of the reference lists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 32 potentially eligible articles, 18 articles were excluded (reasons presented in Chart 1) and 14 remained for final analysis. Two had overlapping data, leaving a total of 12 eligible studies [4,[11][12][13][14][15][16][17][18][19][20][21]. No studies were added from manual search of the reference lists.…”
Section: Resultsmentioning
confidence: 99%
“…The average age ranged from 28.7 to 36 years across cases and from 28 to 52 years across controls. With the exception of a single study in Chinese population [21] and one study in White and African-Americans [12], all studies referred exclusively to Caucasian ancestry. Postpartum VTE was reported from 40% to 80% across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported that the MTHFR C677T or A1298T polymorphism is associated with placental dysfunctions such as recurrent pregnancy loss (RPL), intrauterine growth restriction, preeclampsia, and abruptio placentae [10,11,12,19]. MTR polymorphism 2756 AA was also reported that is associated with elevated plasma homocysteine level and increased RPL risk [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we confirmed that MTHFR is expressed in EVT. Many studies reported MTHFR polymorphism is associated with pregnancy complications such as recurrent pregnancy loss, intrauterine growth restriction, preeclampsia, and abruptio placentae [10,11,12,19]. Meanwhile, it seems that these phenotypes are similar with EVT dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The following numbers of studies were included on the separate thrombophilias: antithrombin deficiency: four cohort studies [17][18][19][20] and seven case-control studies [21][22][23][24][25][26][27] ; protein C deficiency: three cohort studies [18][19][20] and eight case-control studies [21][22][23][24][25][26][27][28][29] ; protein S deficiency: three cohort studies [18][19][20] and eight case-control studies [21][22][23][24][25][26][27][28][29] ; heterozygous factor V Leiden: 17 cohort studies 7-45 and 11 case-control studies ; homozygous factor V Leiden: six cohort studies and six case-control studies ; heterozygous prothrombin G20210A mutation: five cohort studies and 10 case-control studies ; homozygous prothrombin G20210A mutation: one cohort study 31 and three case-control studies ; and compound heterozygous factor V Leiden and prothrombin G20210A mutation: three cohort studies [39][40][41][42][43][44][45][46]…”
Section: Summary Of Selection Processmentioning
confidence: 99%